1987
DOI: 10.1099/0022-1317-68-6-1669
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Structure of Human Interferon  1 (Interferon  II1): Comparison with Other Human Interferons

Abstract: SUMMARYRecombinant human interferon (IFN) col (IFN-~I11) was compared with other human IFNs with regard to antigenic structure, using polyclonal and monoclonal antibodies. Antisera to recombinant IFN-cd or IFN-c~2c cross-neutralized the antiviral activity of other species of IFN-~, but not that of IFN-~ol. Antisera to IFN-/~ or IFN-? likewise had no effect on IFN Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…1) or tro-IFN-fl, but completely neutralized tro-IFN-~.I purified by HP-IAC. The ability of polyclonal anti-human IFN-0t (lymphoblastoid) antiserum to neutralize both the antiviral activities of tro-IFN-0q and tro-IFN-cq[1 can be explained by the fact that IFN-Ctli1 is a component of natural mixtures of lymphoblastoid and leukocyte IFN preparations (Adolf, 1987) used to prepare polyclonal antibodies. The neutralization results support the suggestion (Adolf, 1987) that human type 1 IFN is made up of three antigenically distinct proteins, IFN-cq, IFN-0qi1 and IFN-fl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) or tro-IFN-fl, but completely neutralized tro-IFN-~.I purified by HP-IAC. The ability of polyclonal anti-human IFN-0t (lymphoblastoid) antiserum to neutralize both the antiviral activities of tro-IFN-0q and tro-IFN-cq[1 can be explained by the fact that IFN-Ctli1 is a component of natural mixtures of lymphoblastoid and leukocyte IFN preparations (Adolf, 1987) used to prepare polyclonal antibodies. The neutralization results support the suggestion (Adolf, 1987) that human type 1 IFN is made up of three antigenically distinct proteins, IFN-cq, IFN-0qi1 and IFN-fl.…”
Section: Discussionmentioning
confidence: 99%
“…However, other types of human IFN have been reported by other workers (Wilkinson & Morris, 1983;Dianzani et al, 1986), but these have not been characterized fully. In addition, Adolf (1987) and Hauptmann & Swetly (1985) have reported that a new type of IFN, IFN-og, is released from cells challenged with Sendai virus. This unique IFN (designated IFN-o~I by Adolf, 1987) has 60% sequence identity with human IFN-~ and 26% with IFN-fl, and is different antigenically from human IFN-~, -fl and -% IFN<ol was therefore considered to belong to a subfamily of IFN-~ (Capon et al, 1985) and was termed IFN-~ subclass II (tro-IFN~ii1), in contrast to the classical IFN-~ in IFN-ct subclass I (IFN-~0.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant virus containing the IFN-a2 gene was plaque-purified. The expression of bvIFN-a2 was monitored by analyzing the cell culture supernatant for the presence of secreted IFN-a2 using an IFN-a2-specific ELISA (Adolf et al, 1982;Adolf, 1987).…”
Section: Baculovirus Expression Vectormentioning
confidence: 99%
“…The antiviral assay for the determination of the biological activity of bvIFN-a2 was performed as described (Adolf, 1987).…”
Section: Bioassaymentioning
confidence: 99%
“…One paradoxical property of pig conceptus antiviral activity is that it is partly neutralized by immunoglobulins to human leucocyte IFN (Table 5) but not at all by an antiserum to oTP-1 (not shown). By analogy with the results and hypothesis of Adolf (1987), one cannot exclude the existence of a third sub-class of alpha-related genes, expressed also in induced leucocytes, and to which the pig alpha-like conceptus-derived IFN could belong. On the basis of seroneutralization data, the relative amounts of the two IFN species seem to be different in vivo and in vitro, which suggests either that conceptus synthesis is in some way regulated by the maternal environment, or that the activity of IFN-a-like species could be less stable than that of IFN-.…”
Section: Discussionmentioning
confidence: 95%